Islamic Teachings on Quality Assurance in Islamic Education - Ulfah, Maria; Suharyat, Yayat (International Journal of Global Sustainable Research, 2023)
This paper describes the teachings of Islam in ensuring the quality of Islamic education. Based on the content in Qs. Ar-Ra'du verse 11 which reads: "Allah does not change the condition of a people so that they change the situation that exists in themselves." Most people think that "changing things" often means turning bad luck into good. In fact, Allah has bestowed pleasure on man, but because of man's bad actions, the pleasure turns into a bad thing for man. The author uses a library reaserch approach in studying Qs. Ar-Ra'du verse 11 in relation to quality assurance of Islamic education. The results showed that the quality management of Islamic education is contained in Islamic teachings.